2018
DOI: 10.4070/kcj.2017.0324
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cardiovascular Risks of Dipeptidyl Peptidase-4 Inhibitors: Analyses of Real-world Data in Korea

Abstract: Background and ObjectivesTo compare cardiovascular disease (CVD) risk associated with 5 different dipeptidyl peptidase-4 inhibitors (DPP-4is) in people with type 2 diabetes.MethodsWe identified 534,327 people who were newly prescribed sitagliptin (n=167,157), vildagliptin (n=67,412), saxagliptin (n=29,479), linagliptin (n=220,672), or gemigliptin (n=49,607) between January 2013 and June 2015 using the claims database of the Korean National Health Insurance System. A Cox proportional hazards model was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In our study, there was an increased risk associated with DPP‐4Is compared with α ‐GIs and BGs, but a decreased risk compared with SUs. The inconsistent results may be due, in part, to the different compositions of the endpoint (ie, whether HF or mortality was included or not) or different risks of individual drugs …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, there was an increased risk associated with DPP‐4Is compared with α ‐GIs and BGs, but a decreased risk compared with SUs. The inconsistent results may be due, in part, to the different compositions of the endpoint (ie, whether HF or mortality was included or not) or different risks of individual drugs …”
Section: Discussionsupporting
confidence: 86%
“…However, it is difficult to compare our results with these studies because of different study purposes (class effect vs individual effect), different conditions (monotherapy vs combination therapy), and insufficient sample size for individual drugs due to limited market period in Japan (saxagliptin was introduced in 2013). Additional studies are needed to investigate the risk of individual DPP‐4Is or combined use of DPP‐4Is with other antidiabetic drugs to consider the necessity of regulatory action because of different effects on CVDs among individual DPP‐4Is …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia was defined using the ICD-10 code E78 combined with prescribing lipid-lowering agents at least once a year. 79) In addition to this operational definition, total cholesterol ≥240 mg/dL was another criteria for dyslipidemia. 60) 65) 76) …”
Section: The Operational Definition Of Covariates and Outcomes In Carmentioning
confidence: 99%
“…In this issue, Ha et al 8) reported a very interesting result regarding CVD risk associated with 5 different dipeptidyl peptidase-4 inhibitors (DPP4i) in patients with type 2 diabetes using claims database of the Korean National Health Insurance System. They showed that saxagliptin, linagliptin, and gemigliptin therapies were associated with a lower risk of cardiovascular events compared to sitagliptin therapy.…”
mentioning
confidence: 99%